Beneficial Effects of Deoxyshikonin on Delayed Wound Healing in Diabetic Mice - Jun Yeon Park (International Journal of Molecular Sciences, 2018)
Shiunko ointment is composed of five ingredients including Lithospermi Radix (LR), Angelicae Gigantis Radix, sesame seed oil, beeswax, and swine oil. It is externally applied as a treatment for a wide range of skin conditions such as eczema, psoriasis, hair loss, burns, topical wounds, and atopic dermatitis. Deoxyshikonin is the major angiogenic compound extracted from LR. In this study, we investigated the efficacy of LR extract and deoxyshikonin on impaired wound healing in streptozotocin (STZ)-induced diabetic mice. Treatment with LR extract elevated tube formation in human umbilical vein endothelial cells (HUVECs) and exerted antioxidant activity. An open skin wound was produced on the backs of diabetic mice and was then topically treated with deoxyshikonin or vehicle. In addition, deoxyshikonin promoted tube formation in high glucose conditions exposed to HUVECs, and which may be regulated by increased VEGFR2 expression and phosphorylation of Akt and p38. Our results demonstrate that deoxyshikonin application promoted wound repair in STZ-induced diabetic mice. Collectively, these data suggest that deoxyshikonin is an active ingredient of LR, thereby contributing to wound healing in patients with diabetes.